Monitoramento da rede de abastecimento de água da UFPB - Hollanda, Hudney Guilherme Machado de (2025)
The growing need to improve water management in large public institutions, combined with the search for reducing waste and operating costs, motivated this study, which focused on Campus I of the Federal University of Paraíba (UFPB). The work aimed to implement an automation and monitoring system in the main reservoir of the university's water supply network, which until then was operated manually, subject to failures and without a database for decision-making. The proposal aimed to modernize the operation, improve system control and ensure greater water security for the institution. Level and flow sensors, programmable logic controllers (PLCs) and the ScadaBR supervisory system were used, which allowed real-time monitoring and continuous data collection. The state of the art covered topics such as automation, energy efficiency, intelligent control, monitoring and the use of other technologies applied to the automation and monitoring of water supply systems. The results showed that artesian wells provided, on average, 66.62% of the water consumed by the institution, reducing dependence on the local utility company and reducing supply failures. It was also possible to build a useful database for management. The savings generated by reducing the utility company's consumption were estimated at approximately R$250,000.00 per month. The study showed that automation brought significant improvements to the system, both in operational and financial aspects.